2001
DOI: 10.1074/jbc.m005486200
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of ERK and p38 MAPK Inhibitors Ablate Tumor Necrosis Factor-α (TNF-α) mRNA Induction

Abstract: Tumor necrosis factor-␣ (TNF-␣) is a potent proinflammatory cytokine whose synthesis and secretion are implicated in diverse pathologies. Hence, inhibition of TNF-␣ transcription or translation and neutralization of its protein product represent major pharmaceutical strategies to control inflammation. We have studied the role of ERK and p38 mitogen-activated protein (MAP) kinase in controlling TNF-␣ mRNA levels in differentiated THP-1 cells and in freshly purified human monocytes. We show here that it is possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
110
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 39 publications
20
110
0
Order By: Relevance
“…Ex vivo production of TNF␣ and IL-1␤ was further suppressed by the presence of both kinase inhibitors. The requirement for the inhibition of both ERK and p38 MAPK pathways for the strong suppression of LPS-induced TNF␣ production (40,53) is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ex vivo production of TNF␣ and IL-1␤ was further suppressed by the presence of both kinase inhibitors. The requirement for the inhibition of both ERK and p38 MAPK pathways for the strong suppression of LPS-induced TNF␣ production (40,53) is consistent with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Several investigators demonstrated that PD98059, an inhibitor of MEK, suppressed TNF␣ production in LPS-stimulated or CD154-stimulated monocytes (36)(37)(38)(39). Conversely, it has been reported that p38 is involved not only in the translation, but also in the stabilization of TNF␣ mRNA (40)(41)(42). These findings are in accordance with the results of the present study, that activation of both ERK and p38 is important for TNF␣ production by CD154 plus IFN␥-stimulated CD14ϩ synovial cells and for ex vivo TNF␣ production by freshly isolated synovial cells from RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, all three MAPK signaling pathways (ERK, JNK, and p38 MAPK) are involved in the transcription of TNF-a mRNA after LPS induction, and activation of each MAPK signal leads to full induction of the TNF-a gene. [52][53][54] Based upon two aspects of our present results, we suggest that ERK and p38 MAPK are pivotal signaling events in the mediation of DcR3 response. First, MEK inhibitors (PD98059 and U0126) and a p38 MAPK inhibitor (SB203580) can inhibit DcR3-elicited TNF-a synthesis and osteoclast formation.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast, the effect of LPS on stimulation of TNF-␣ expression in RAW 264.7 cells was not affected by U0126. These findings are consistent with reports demonstrating that in addition to ERK 1/2, LPS-induced TNF-␣ expression occurs via p38 (2,45) and JNK (3,29) signaling. In contrast, C. pneumoniae antigens did not activate JNK and p38 kinases in this study (Fig.…”
Section: Discussionsupporting
confidence: 93%